Decarbonizing the UK energy system and the implications for UK shipping. Issue 6 (December 2012) - Mander, Sarah; Walsh, Conor; Gilbert, Paul; Traut, Michael; Bows, Alice
Background: The current UK energy system relies heavily on shipped imports of fossil fuels. As climate change policies drive energy system decarbonization, fuel imports are likely to change.Results: Based upon future energy scenarios devised by the UK's Department of Energy and Climate Change and a set of contrasting trading assumptions, this article explores the impact of energy system decarbonization upon freight work and CO2 emissions arising from fuel shipping. While oil and oil products are currently the most important contributors to both freight work and shipping CO2 emissions, by 2050 biofuels and biomass will become dominant energy commodities.Conclusion: The distance over which fuel travels is important and the greatest reductions in absolute CO2 emissions are achieved when fuel is sourced close to the UK.